Invented spelling in preschool: Contributions for learning to read and write - Albuquerque, Ana (2018)
This study was developed within the theoretical framework of emergent literacy and aims at analysing the contributions of an invented spelling intervention programme in preschool for learning to read and write in the first year of primary school. 95 children attending the last year of preschool who did not know how to read or write participated in this study and were randomly divided into two conditions: 48 in the experimental group and 47 in the control group. The participants in each condition were equivalent on age, parents’ education level, abstract reasoning, syllabic awareness, phonemic awareness and letter knowledge. Children’s word reading and writing skills were tested in preschool (before and after the programme) and at the end of primary school. During the intervention period, the experimental group participated in 10 invented spelling biweekly sessions, whereas the control group participated in storytelling activities. Data analysis exposed statistically significant differences both in reading and in writing, since the experimental group displayed higher results at the end of primary school and at the end of Year 1. This study indicates that it is important to include invented spelling activities as a pedagogical practice in preschool contexts.